Pemodelan Perkuatan Menggunakan Bambu Untuk Daya Dukung Pondasi Dangkal pada Tanah Gambut - Yulindasari Sutejo; Sutanto Muliawan; Ratna Dewi; Febrian Hadinata; Budi Ariawan; Reffanda Kurniawan Rustam (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2021)
Some of the unfavorable characteristics of peat soil are low bearing capacity and high compressibility. The reinforcing material used in this research which functions the same as geogrid are bamboo materials (grids and woven). The bamboo material used aims to determine the carrying capacity and reduction of shallow foundations on peat soil before being reinforced and after being reinforced. Bamboo matting and rectangular patterned bamboo grids. Laboratory scale testing were used as the research methodology. The peat soil sampling location came from the area of Dusun III Banyu Urip, Banyuasin Regency, South Sumatra Province. The bamboo material is obtained from the Seberang Ulu area, Palembang City and sand is obtained from the sand depot in the Musi II area, Palembang City. The results of laboratory testing show that the addition of the number of reinforcement layers and the effective layer depth distance will give a greater bearing capacity ratio (BCR) value. The bearing capacity value of the shallow foundation before being reinforced on peat soil using Terzaghi's analysis is 45.232 kpa. Then, after testing the variation in the depth of the layer d = 0b; d = 0.25b; and d = 0.5b with the number of layers 1 layer, 2 layers and 3 layers obtained a variation which gives the highest bearing capacity value of layer depth variations d = 0.25b with the number of layers of 3 layers. The bearing capacity value is 94 kpa with a BCR value of 2.08 (percent increase of 107.96 %).